Comment on: “Theoretical calculation of turn-on delay time of VCSEL and effect of carriers recombination” [Opt. Laser Technol. 39 (2007) 997–1001] - Hisham, H.K.; Abas, A.F.; Mahdiraji, Ghafour Amouzad; Mahdi, M.A.; Muhammad Noor, A.S. (Elsevier, 2012)
Zhang et al. [Opt.Laser Technol.39 (2007) 997–1001], through theoretical calculation,have shown that the turn-on time delay can be reduced by increasing any of the non-radiative (Anr), radiative (B), and/or Auger recombination (C) coefficients at a constant injection current over threshold current.Here,we explain that the results presented by that paper are incorrect and the turn-on time delay increases by increasing any of the carrier recombination rate coefficients.